Signic trans/re/formulations of Deleuzian dream-image in Katy Perry’s videoclip E.T. - Guimarães, Denise Azevedo Duarte (2016)
This article discusses the techno-aesthetic interlocutions between audiovisual products and cinema, for proposing an analysis of the fantastic, futuristic and oneiric narrative of Katy Perry’s videoclip E.T. (2011). Gilles Deleuze’s notion of timeimage, in the signic instance of dream-image, is the main theoretical basis of this paper. The dialogue with Charles Sanders Peirce is essential to understand the Deleuzian “onirosigns” in the chosen music video.To develop the intended reflections, are used theoretical contributions from researchers of audiovisual languages and new media.Finally, in order to interpret the spatio-temporal modulations of dreamlike and post-utopian narrative on the screen, the mitopoetical images are analyzed on the basis of phenomenological concepts.